"ADJUSTMENT STRATEGIES IN WORKING ENVIRONMENT OF SELF-INITIATED EXPATRIATE TEACHERS OF ENGLISH LANGUAGE IN HANOI: A QUALITATIVE INVESTIGATION = Chiến lược thích nghi văn hóa trong môi trường làm việc của giáo viên tiếng Anh ngoại quốc tại Hà Nội, Việt Nam: một nghiên cứu định tính " - Nguyễn, Xuân Hạnh (2020)
NFL Project 2020 addressed Vietnam‟s compelling need for improving communication in English that, as a consequence, has transformed the country as a destination for “self-initiated expatriate (SIE)” English teachers. They are the people who choose to set out to work in a foreign country without the assignment or the help of a home company. Analyzing the content of transcripts and field notes from six semi-structured individual interviews with six selfinitiated expatriate teachers of English who have spent from about 9 months to 7 years in Hanoi about their process of adjusting to culture in the Vietnamese workplace, this study provides researchers, HRM practitioners, and policy makers an insight into the self-initiated expatriate work life in this South-East Asian country. Participants exhibited a passive approach to cultural adjustment, a lack of preparation, tendency to display ethnocentrism, and reported a critical need for better training, job descriptions and organizational support. The findings suggest that further research and certain HRM practices should be conducted to encourage integration between Vietnamese teachers and managers and this diverse group of foreign teachers, not only to foster a work environment that embraces support and diversity, but also to ensure the quality of the English training programs they are directly involved with as teachers.